OPTIMIZATION OF THE CONE BIT OF SPHERICAL FLOATING SLEEVE BASED ON RESPONSE SURFACE METHODOLOGY - HE Wei; SHEN PingSheng; LI HuaChuan; CHEN Yang; HE JunChao; HUANG Shuai (Jixie qiangdu)
In order to improve the life of the cone bit sliding bearing,eliminates the edge stress concentration phenomenon of the spherical floating sleeve end portion,the circular groove structure of Spherical floating sleeve was optimized by the combination of response surface methodology and the finite element method. the objective function was established by along the contact line of the middle stress σmand end stress σedifference between the floating sleeve of outer spherical surface and inner surface,σ1、σ2 was called objective function,The distance from the center of the circular groove to the floating sleeve surface h and the radius r of the circular groove and the distance from the center of the circular groove to the end face of the floating sleeve t was design variable,so the optimization of mathematical model was established. By regression analysis model,obtained the circular groove of optimal controllably parameters: r = 0. 53 mm、t = 0. 07 mm、h = 1. 10 mm. The finite element simulation analysis verified the reliability of optimal structure parameters,The results show that the optimized spherical floating sleeve of the inner surface and outer spherical surface of contact stress distributes more uniformity and reduces the edge stress concentration.